Ionic liquid redox electrolytes based on binary mixtures of 1-alkyl-methylimidazolium tricyanomethanide with 1-methyl-3-propylimidazolium iodide and implication in dye-sensitized solar cells - Bidikoudi, M.; Stergiopoulos, T.; V. Likodimos; Romanos, G.E.; Francisco, M.; Iliev, B.; Adamová, G.; Schubert, T.J.S.; P. Falaras (Journal of Materials Chemistry A, 2013)
Innovative redox electrolytes for dye-sensitized solar cells (DSCs) were prepared using binary mixtures of 1-methyl-3-propylimidazolium iodide (MPII) with 1-alkyl-methylimidazolium tricyanomethanide, CνmimTCM (ν = 2, 4, 6, 8) ionic liquids (ILs) to lower the high viscosity of MPII. The investigation of the physicochemical properties of the IL blends as a function of temperature has shown that both density and viscosity strongly depend on the kind of the Cνmim cation in the mixture. The corresponding Raman spectra were dominated by the vibrational modes of the IL components in an additive way and confirmed the absence of any specific interaction, independent of the Cν alkyl chain length. The electrochemical properties (triiodide diffusion coefficients, specific conductivity), determined in symmetrical thin layer cells using polarization and electrochemical impedance spectroscopy (EIS) measurements, have shown that both diffusion and conductivity decreased with increasing viscosity, and further confirmed the electrolytes' compatibility with the cathode. Incorporation of the novel electrolytes in DSC devices revealed a systematic dependence of the cell photovoltaic performance on the alkyl chain length of CνmimTCM; the maximum power conversion efficiency exceeded 5 and 6.5% under 1 and 0.1 sun AM 1.5 G illumination, respectively, for the ionic liquid with the shortest alkyl chain. The solar cells were further characterized by EIS (IMPS) spectroscopy, exploring charge recombination dynamics and identifying conduction band edge shifts. Solidification of the electrolytes with silica nanoparticles, demonstrated that the ionic liquid electrolytes with long chain length (ν > 4) not only retain their efficiencies, but also exhibit a 22% efficiency enhancement, which is most pronounced for the electrolytes employing ionic liquids with the longest (hexyl- and octyl-) alkyl chains. © 2013 The Royal Society of Chemistry.
cited By 16